Low carbon building performance in the construction industry: a multi-method approach of system dynamics and building performance modelling. Issue 9 (1st September 2020) - Papachristos, George; Jain, Nishesh; Burman, Esfandiar; Zimmermann, Nici; Wu, Xiaoying; Liu, Pei; Mumovic, Dejan; Lin, Borong; Davies, Mike; Edkins, Andrew
Abstract: The construction industry contributes significantly to energy consumption and carbon emissions. Moreover, people spend more time inside buildings, so their health is increasingly influenced by indoor environmental conditions. When considered through these lenses, the concept of total building performance can span energy consumption, the associated CO2 emissions, and indoor environmental quality (IEQ). At the individual project level, building underperformance with respect to energy and IEQ is frequent, and the ex post performance gap is partially attributed to the construction project management and operations phase of the building lifecycle. This underperformance motivates the research of this paper into the construction process outcomes in terms of energy performance and IEQ, and ways to reduce the performance gap. The paper develops a multi-methodology framework to analyse the effect of building development project process on energy performance and IEQ from an operations management perspective. The framework couples system dynamics modelling of construction project management to building performance modelling. The paper details the way they are coupled, the application steps and data requirements, so that they can be applied on a case by case basis. The aim is to combine operations management to building performance disciplines and deliver insights for industry practitioners and policy makers.